2005
DOI: 10.3133/sir20045090
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of trace-element concentrations and occurrence of metallurgical slag particles in accumulated bed sediments of Lake Roosevelt, Washington, September 2002

Abstract: Inset 1: Retrieval of 40 centimeter sediment core including lacustrine and pre-reservoir soil sediments near Marcus, Washington.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 7 publications
(10 reference statements)
2
17
0
Order By: Relevance
“…These metals are minor components of slag but were substantial components of liquid effluents. Cox et al (2004) noted decreases of Pb, Cd, and other metals in surficial layers of sediment cores of reservoir sediments, consistent with decreases of approximately 99% in the release of metals in liquid effluents between 1977 and 2003. Conversely, they reported that Cu concentrations generally increased in surficial layers of reservoir sediments, suggesting that weathering and/or transport of slag particles remains an important internal source of Cu from the riverine reach to the reservoir.…”
Section: Characteristics Of Sediment and Porewatersupporting
confidence: 58%
See 2 more Smart Citations
“…These metals are minor components of slag but were substantial components of liquid effluents. Cox et al (2004) noted decreases of Pb, Cd, and other metals in surficial layers of sediment cores of reservoir sediments, consistent with decreases of approximately 99% in the release of metals in liquid effluents between 1977 and 2003. Conversely, they reported that Cu concentrations generally increased in surficial layers of reservoir sediments, suggesting that weathering and/or transport of slag particles remains an important internal source of Cu from the riverine reach to the reservoir.…”
Section: Characteristics Of Sediment and Porewatersupporting
confidence: 58%
“…Cox et al (2004) concluded that metals in sediments from the reservoir reach originated predominantly from aqueous effluents, rather than from slag particles. These differences are consistent with the occurrence of different physicochemical forms of metals, which reflect different types of source materials.…”
Section: Characteristics Of Sediment and Porewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in the river flow, as a result of the operation of upriver hydroelectric dams, annual spring high river flows, and occasional floods, have resulted in the resuspension, relocation, and subsequent redeposition of the sediment (BNWL-2305). Upper-layer sediment in the Columbia River downstream of the Hanford Site contains low concentrations of radionuclides and metals of Hanford Site origin as well as radionuclides from nuclear weapons testing fallout, and metals and other nonradioactive contaminants from mining and agricultural activities (Beasley et al 1981; BNWL-2305; PNL-8148; PNL-10535; Cox et al 2004). Periodic sediment sampling confirms that concentrations are low and that no significant changes in concentrations have occurred.…”
Section: Monitoring Of Columbia River Sedimentmentioning
confidence: 87%
“…Approximately 12 million metric tons of smelter slag, along with effluents, reportedly were discharged to the UCR between approximately 1930 and 1995 from a large smelter facility located in Trail, British Columbia, approximately 16 km north of the United States-Canadian border (Cox et al 2005; Teck American Incorporated [TAI] 2008). A large percentage of these materials are now found in the UCR as weathered slag dominated by sandsized and smaller particles that are enriched with several heavy metals, including cadmium (Cd), copper (Cu), zinc (Zn), and lead (Pb) (Johnson et al 1988(Johnson et al , 1990Johnson 1991;Bortleson et al 1994).…”
mentioning
confidence: 99%